Climate Change and Poverty : An Integrated Strategy for Adaptation - Cord, Louise; Hull, Catherine; Hennet, Christel; Van der Vink, Gregory (World Bank, Washington, DC, 2012)
Developing countries are most exposed to the impact of climate change and within these countries, the poor face the brunt of the burden. Climate change is not a discrete problem that can be dealt with through isolated reforms: impacting economic growth, health, and institutional capacity, it represents a full-frontal challenge to development. This note traces the multi-dimensional impacts of climate change, particularly on the poor, and proposes a three pronged integrated response to promote adaptation and help poor households cope with related risks.